2021
DOI: 10.2147/nss.s326880
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Insomnia in Chinese Mental Health Professionals During the COVID-19 Pandemic: A Cross-Sectional Study

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is associated with increased risk of insomnia symptoms (insomnia hereafter) in health-care professionals. Network analysis is a novel approach in linking mechanisms at the symptom level. The aim of this study was to characterize the insomnia network structure in mental health professionals during the COVID-19 pandemic. Patients and Methods: A total of 10,516 mental health professionals were recruited from psychiatric hospitals or psychiatric units of general hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 53 publications
(77 reference statements)
1
20
2
3
Order By: Relevance
“…The central symptoms can also be intervention targets in treating the disorder. While a positive edge between two symptoms represents the co-occurrence between them and a strong edge indicates that both symptoms may be strongly connected, targeting either of them can improve the other symptom ( 15 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The central symptoms can also be intervention targets in treating the disorder. While a positive edge between two symptoms represents the co-occurrence between them and a strong edge indicates that both symptoms may be strongly connected, targeting either of them can improve the other symptom ( 15 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…11 A number of other studies have explored sleep in relation to depression in specific contexts, for instance, low energy and difficulty maintaining sleep/earlymorning awakening were identified as bridge symptoms in Wenchuan earthquake survivors at a 10-year follow-up 12 ; sleep problems were identified to have the highest clinical relevance in a study in psychiatric healthcare professionals during the COVID-19 pandemic. 13 Insomnia symptoms were most strongly associated with neuroticism and conscientiousness in a network of personality traits. 14 Cognitive therapy (CT) and behavioural therapy (BT) for insomnia show different symptom-specific effects (sleep efficiency; difficulty maintaining sleep; dissatisfaction with sleep for BT, and interference with daily functioning; difficulty initiating sleep; early morning awakenings; and worry about sleep for CT) 15 while, in a separate study, sleep related behaviours were associated with BT, and worry; impaired quality of life (QOL); dysfunctional beliefs; monitoring sleep-related threats for CT. 16 To our knowledge, only one prior published network analysis has investigated insomnia symptoms discretely in relation to both depression and anxiety symptoms.…”
Section: Introductionmentioning
confidence: 98%
“…Although several studies using the network approach have probed the association patterns of various psychiatric conditions among different subpopulations during the COVID-19 pandemic ( Bai et al, 2021 ; Di Blasi et al, 2021 ; Li et al, 2022 ; Wang et al, 2020 ), few have focused on tourism-dependent areas like Macao. Previous studies revealed that the network structure of mental health symptoms in various subpopulations might differ by age, gender, or health status ( Hartung et al, 2019 ; Shim et al, 2020 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%